Comparison of metal free polymer–dye conjugation strategies in protic solvents. Issue 17 (15th April 2016) - Gaitzsch, Jens; Delahaye, Maarten; Poma, Alessandro; Du Prez, Filip; Battaglia, Giuseppe
Abstract : Introducing the TAD chemistry to the field of polymer–dye conjugations to broaden the toolbox of metal- and additive-free linking methods. Abstract : Polymer–dye conjugations are one of the common examples for polymer modifications. They represent a crucial step for imaging in optical microscopy or for tracing and marking macromolecules. In this work, we present a comparison between quick and efficient conjugation reactions that do not rely on the use of a metal catalyst, which could contaminate the resulting polymer and hinder its use for subsequent biological applications. Moreover, since the conjugation strategy needs to be compatible with the solvent system used to solubilise the polymer, we focussed our attention on assessing these conjugation approaches for their feasibility with a sample polymer that is only soluble in protic solvents. The methods studied include the ring-strain promoted azide–alkyne click reaction, thiol/maleimide conjugation as well as the 1, 2, 4-triazoline-3, 5-dione (TAD) with a diene moiety, one of the latest click chemistries available.